Dyscephalia mandibulo-oculo-facialis: Hallermann-Streiff syndrome: a case report - Eke, Nilüfer (The Turkish Journal of Pediatrics, 1967)
A case of dyscephalia mandibulo-oculo-facialis is presented. The patient had the characteristic bird face, microcephaly, mental and motor retardation and congenital bilateral cataract. Chromosome analysis revealed no anomalies. She had cortical atrophy proven by pneumoencephalography.